A survey of GP views on intra-uterine contraception. Issue 2 (1st April 2000) - Gupta, Sunanda; Miller, John E
Abstract : Aims: To investigate knowledge and attitudes towards intra-uterine contraception. Design: Anonymous postal survey of 441 GPs (153 female and 288 male GPs) from the FHSA register in Stockport and Manchester. Setting: General practices in Stockport and Manchester. Main outcome measure: Response to a series of questions concerning attitudes and knowledge of intra-uterine contraception. Results: One hundred and forty-two responses were received, giving a 35% response rate. Thirty-four percent of responding GPs did not fit intra-uterine devices (IUDs), with only 10% fitting more than 30 a year. There was a significant trend against IUD fitting by male GPs and GPs aged <40 years. Younger GPs with <10 years experience were significantly more aware of the reliability of intra-uterine contraception, but perceived IUD fitting as inconvenient for both the patient and the doctor. Female GPs had better knowledge and more positive attitudes to IUDs than male GPs. Conclusion: GPs may have difficulties in maintaining expertise. Primary care groups may opt to concentrate fittings in a few expert practices, or refer women to centrally based family planning clinics for IUD fitting.